A novel approach to surface electromyography: an exploratory study of electrode-pair selection based on signal characteristics - Kendell, Cynthia; Lemaire, Edward D; Losier, Yves; Wilson, Adam; Chan, Adrian; Hudgins, Bernie (Université d'Ottawa | University of Ottawa, 2012)
Abstract A 3 × 4 electrode array was placed over each of seven muscles and surface electromyography (sEMG) data were collected during isometric contractions. For each array, nine bipolar electrode pairs were formed off-line and sEMG parameters were calculated and evaluated based on repeatability across trials and comparison to an anatomically placed electrode pair. The use of time-domain parameters for the selection of an electrode pair from within a grid-like array may improve upon existing electrode placement methodologies.